The role of apical cell–cell junctions and associated cytoskeleton in mechanotransduction. (13th March 2017) - Sluysmans, Sophie; Vasileva, Ekaterina; Spadaro, Domenica; Shah, Jimit; Rouaud, Florian; Citi, Sandra
Review: In this review article, Sluysmans et al. summarize past and recent advancements in understanding the composition and organization of molecular machineries which connect the actin and microtubule cytoskeletons to tight and adherens junctions of vertebrate epithelial and endothelial cells, and the role of the cytoskeleton in the functions of these junctions. The implication of specific junctional proteins in mechanotransduction processeses in epithelial and endothelial cells is also reviewed. Abstract : Tissues of multicellular organisms are characterised by several types of specialised cell–cell junctions. In vertebrate epithelia and endothelia, tight and adherens junctions (AJ) play critical roles in barrier and adhesion functions, and are connected to the actin and microtubule cytoskeletons. The interaction between junctions and the cytoskeleton is crucial for tissue development and physiology, and is involved in the molecular mechanisms governing cell shape, motility, growth and signalling. The machineries which functionally connect tight and AJ to the cytoskeleton comprise proteins which either bind directly to cytoskeletal filaments, or function as adaptors for regulators of the assembly and function of the cytoskeleton. In the last two decades, specific cytoskeleton‐associated junctional molecules have been implicated in mechanotransduction, revealing the existence of multimolecular complexes that can sense mechanical cues and translate them into adaptation to tensile forces and biochemical signals. Here, we summarise the current knowledge about the machineries that link tight and AJ to actin filaments and microtubules, and the molecular basis for mechanotransduction at epithelial and endothelial AJ.